Respuesta :
The first equation is of degree 5 so has a total of 5 roots. It has 3 real roots
and 2 complex roots.
Second equation 2 complex roots.
Third has 4 complex roots
fourth has 7 complex roots
fifth has 3 complex roots
and 2 complex roots.
Second equation 2 complex roots.
Third has 4 complex roots
fourth has 7 complex roots
fifth has 3 complex roots
Answer:
2, 2, 4, 6, 4
Step-by-step explanation:
Fundamental Theorem of Algebra states that 'An 'n' degree polynomial will have n number of real roots'.
1. The polynomial is given by [tex]x(x^2-4)(x^2+16) = 0[/tex]
So, on simplifying we get that, [tex]x(x+2)(x-2)(x^2+16)=0[/tex].
Since, degree of polynomial is 5, it will have 5 roots.
This gives us that the roots of the equation are x = 0, -2, 2, 4i and -4i
So, the number of complex roots are 2.
2. The polynomial is given by [tex](x^2+4)(x+5)^2 = 0[/tex]
Since, degree of polynomial is 4, it will have 4 roots.
Equating them both by zero, [tex](x^2+4)= 0[/tex] and [tex](x+5)^2=0[/tex] gives that the roots of the polynomial are x = 2i, -2i, -5, -5.
So, the number of complex roots are 2.
3. The polynomial is given by [tex]x^6-4x^5-24x^2+10x-3=0[/tex]
Since, degree of polynomial is 6, it will have 6 roots.
On simplifying, we get that the real roots of the polynomial are x = -1.75 and x = 4.28.
So, the number of complex roots are 6-2 = 4.
4. The polynomial is given by [tex]x^7+128=0[/tex]
Since, degree of polynomial is 7, it will have 7 roots.
On simplifying, we get that the only real root of the polynomial is x = -2.
So, the number of complex roots are 7-1 = 6.
5. The polynomial is given by [tex](x^3+9)(x^2-4)=0[/tex]
Since, degree of polynomial is 5, it will have 5 roots.
Simplifying the equation gives [tex](x+2)(x-2)(x+\sqrt[3]{9})(x^2-\sqrt[3]{9x}+9^{\frac{2}{3}})=0[/tex]
Equating each to 0, we get the real roots of the polynomial is [tex]x=-3^{\frac{2}{3}}[/tex]
So, the number of complex roots are 5-1 = 4